(untitled) (Review Journal of Neurological & Medical Sciences Review, 2025)
Over the past four decades, nanotechnology has experienced exponential growth and continues to advance with sustained momentum. The integration of nanoscale innovations into diverse sectors has fundamentally transformed multiple facets of modern life, ranging from healthcare to the agri-food industry. Engineered nanoparticles have enabled notable advancements, including the substantial extension of food shelf life, enhanced intracellular transport of poorly water-soluble pharmaceutical compounds, and increased therapeutic efficacy of targeted agents such as chemotherapeutics. As a result, nanotechnology has exerted a profound influence on global quality of life and has introduced significant shifts in economic paradigms. This review critically examines the physicochemical properties of nanoparticles that underpin both their functional advantages and potential cytotoxicity. Emphasis is placed on the utilization of nanoparticles across biological disciplines, with particular focus on their roles in drug delivery platforms and the field of nanomedicine. Additionally, the review explores nanoformulations and delivery systems that have attained regulatory approval by the U.S. Food and Drug Administration (FDA). The implications of sustained human and environmental exposure to nanoparticles, due to their increasing prevalence in consumer and clinical products, are also considered. Strategies to mitigate adverse effects while maintaining technological progress are highlighted to support safe and sustainable nanotechnology applications. Keywords: Nanotechnology; nanoparticles, Nanoformulation, drugs administration, nanomedicine